SCNT Method and the Application for Patent Eligibility on Cloned Animals - Swazo, Norman K. (Bangladesh Journal of Bioethics, 2016)
Patents recognize economic right and are important for both individual and social economic benefit. Nonetheless, mere economic right does not eliminate the requirement for moral assessment when adjudicating intellectual property claims, especially in the case of claims associated with applications of biomedical technology [e.g., somatic cell nuclear transfer (SCNT) methods]. This is so for applications for patent in the case of live-born animal clones, as governed in the setting of the judicial system of the USA. Here recent federal court decisions in the USA are reviewed, and the ethical ambiguities of this judicial review are engaged in light of the current prohibitions on human reproductive cloning. It is concluded that the legal proscription of patents on animal clones bodes well for human accountability to present and future generations in the event of human reproductive cloning.